2006
DOI: 10.1038/nature04544
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the non-haem iron halogenase SyrB2 in syringomycin biosynthesis

Abstract: Non-haem Fe(II)/alpha-ketoglutarate (alphaKG)-dependent enzymes harness the reducing power of alphaKG to catalyse oxidative reactions, usually the hydroxylation of unactivated carbons, and are involved in processes such as natural product biosynthesis, the mammalian hypoxic response, and DNA repair. These enzymes couple the decarboxylation of alphaKG with the formation of a high-energy ferryl-oxo intermediate that acts as a hydrogen-abstracting species. All previously structurally characterized mononuclear iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
576
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 363 publications
(599 citation statements)
references
References 25 publications
18
576
2
3
Order By: Relevance
“…An interesting attribute of clp-and Clp-containing triple helices is that they could be modified covalently by the S N 2 attack of nucleophiles at the halogenated carbon. Finally, we note the similarity of the active site and reactivity of mammalian P4H, the enzyme responsible for hydroxylation of Pro residues in natural collagen, 76 and the non-haem iron halogenase SyrB2, 77 an enzyme responsible for the chlorination of unactivated carbon atoms. 78 As Clp confers thermal stability on collagen triple helices at a level similar to that of Hyp, it is possible that organisms evolving in an environment rich in chloride ions could evolve stable chlorinated collagens analogous to the hydroxylated collagens found in modern animals.…”
Section: Discussionmentioning
confidence: 90%
“…An interesting attribute of clp-and Clp-containing triple helices is that they could be modified covalently by the S N 2 attack of nucleophiles at the halogenated carbon. Finally, we note the similarity of the active site and reactivity of mammalian P4H, the enzyme responsible for hydroxylation of Pro residues in natural collagen, 76 and the non-haem iron halogenase SyrB2, 77 an enzyme responsible for the chlorination of unactivated carbon atoms. 78 As Clp confers thermal stability on collagen triple helices at a level similar to that of Hyp, it is possible that organisms evolving in an environment rich in chloride ions could evolve stable chlorinated collagens analogous to the hydroxylated collagens found in modern animals.…”
Section: Discussionmentioning
confidence: 90%
“…If not, what factors ensure the strict halogen-rebound selectivity? The failure of attempts to detect the alcohol products of competing hydroxyl-radical rebound answered the first question in the negative (12,14). The report that the A118E variant of SyrB2, with the carboxylate ligand of the facial triad restored, is not an efficient hydroxylase (14) suggested that additional adaptations, beyond the manifest carboxylate 3 halide iron ligand swap, must have accrued during the evolutionary divergence of the halogenases and hydroxylases to distinguish their outcomes.…”
mentioning
confidence: 99%
“…Sequence analysis and the crystal structure of SyrB2 (14), the halogenase that supplies the 4-chloro-L-threonine fragment incorporated into syringomycin E (a phytotoxin produced by Pseudomonas syringae B301D) (12), revealed that it lacks the carboxylate ligand, having an Ala residue where the contributing Asp or Glu would normally be found (Scheme 1 A). The observation that a halide ion (X Ϫ ) coordinates to the Fe(II) cofactor at the vacated site suggested a related mechanism for the halogenase reaction involving abstraction of H • from the substrate by the oxo group of a haloferryl intermediate and rebound of the coordinated halogen radical from the resultant X-Fe(III)-OH complex to the substrate radical (green arrows).…”
mentioning
confidence: 99%
“…Initial insight into their catalytic mechanism was derived from the crystal structure of SyrB2, which chlorinates the γ-methyl group of L-threonine in syringomycin biosynthesis. 48 The Fe center is coordinated by two protein-derived histidines, bidentate αKG, water, and chloride. The carboxylate of the "facial triad" that normally coordinates the Fe(II) center is replaced by an alanine in the protein primary structure, presenting a coordination site for the chloride ligand.…”
Section: αKg-dependent Halogenasesmentioning
confidence: 99%